Comparative Analysis of the Safety and Functional Outcomes of Anterior versus Retropupillary Iris-Claw IOL Fixation - Paolo Mora; Giacomo Calzetti; Stefania Favilla; Matteo Forlini; Salvatore Tedesco; Purva Date; Viola Tagliavini; Arturo Carta; Rino Frisina; Emilio Pedrotti; Stefano Gandolfi (Journal of Ophthalmology)
Purpose. To compare the functional and clinical outcomes of the iris-claw intraocular lens (IOL) placed on the anterior versus posterior surface of the iris. Patients and Methods. A multicenter, retrospective study. Data on eyes that underwent anterior or retropupillary iris-claw IOL implantation because of inadequate capsular support secondary to complicated cataract surgery, trauma, and dislocated/opacified IOLs since January 2015 were analyzed. For study inclusion, evaluation results had to be available in the medical records both preoperatively and at 1 and 12 months after implantation. The following parameters were compared between the groups: best-corrected distance visual acuity (BCDVA), spherical and cylindrical refractive error, endothelial cell density (ECD), central macular thickness (CMT), and percentage and type of postoperative complications. Results. In total, 60 eyes of 60 patients aged 73 ± 13 years were included: 28 eyes (47%) involved anterior, and 32 eyes (53%) retropupillary, iris-claw IOL fixations. Preoperatively, the groups were similar in all parameters except for a significantly higher proportion of retropupillary fixations in patients who had previously experienced a closed-globe trauma (p=0.03). The groups showed comparable improvements in BCDVA after surgery (final BCDVA: 0.34 ± 0.45 vs. 0.37 ± 0.50 logMAR in the anterior and retropupillary placement groups, respectively). During follow-up, no group difference was observed in refractive error or CMT. Both groups experienced similarly marked ECD loss and showed similar incidence of postoperative complications, with cystoid macular edema being the most common complication. Multivariable linear regression showed that BCDVA at 1 month was the best predictor of the final BCDVA. Conclusions. Anterior chamber and posterior chamber iris-claw IOL fixations proved equally effective and safe for aphakic correction in eyes with inadequate capsular support.